2011
DOI: 10.1016/j.cell.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Human Flap Endonuclease Structures, DNA Double-Base Flipping, and a Unified Understanding of the FEN1 Superfamily

Abstract: SUMMARY Flap endonuclease (FEN1), essential for DNA replication and repair, removes RNA and DNA 5′-flaps. FEN1 5′ nuclease superfamily members acting in nucleotide excision repair (XPG), mismatch repair (EXO1) and homologous recombination (GEN1) paradoxically incise structurally distinct bubbles, ends or Holliday junctions, respectively. Here structural and functional analyses of human FEN1:DNA complexes show structure-specific, sequence-independent recognition for nicked dsDNA bent 100° with unpaired 3′- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
520
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(548 citation statements)
references
References 57 publications
27
520
0
1
Order By: Relevance
“…Analysis of the structures of FEN1 (Tsutakawa et al 2011) and EXO1 (Orans et al 2011), which were solved at similar times, suggest a unified mechanism for this type of nuclease involving DNA bending and two nucleotide 'fraying' of one strand (Orans et al 2011).…”
Section: Fen1mentioning
confidence: 93%
See 1 more Smart Citation
“…Analysis of the structures of FEN1 (Tsutakawa et al 2011) and EXO1 (Orans et al 2011), which were solved at similar times, suggest a unified mechanism for this type of nuclease involving DNA bending and two nucleotide 'fraying' of one strand (Orans et al 2011).…”
Section: Fen1mentioning
confidence: 93%
“…Furthermore, FEN1 has recently been crystallised both alone (Sakurai et al 2008;Tsutakawa et al 2011) and in association with the Rad9-Rad1-Hus1 (9-1-1) DNA damage checkpoint complex (Dore et al 2009). Analysis of the structures of FEN1 (Tsutakawa et al 2011) and EXO1 (Orans et al 2011), which were solved at similar times, suggest a unified mechanism for this type of nuclease involving DNA bending and two nucleotide 'fraying' of one strand (Orans et al 2011).…”
Section: Fen1mentioning
confidence: 99%
“…These 5′ flaps are generated during lagging strand DNA synthesis or during long-patch base excision repair. The FEN1 substrates are in fact double-flap DNA (dfDNA) with DNA on the opposite side of the 5′ flap, forming a single nucleotide 3′ flap when bound to the enzyme (2,3). By removing the 5′ ssDNA or RNA flap from such substrates, FEN1 produces a single nicked product that could be sealed by the subsequent action of a DNA ligase (4).…”
mentioning
confidence: 99%
“…Though structural snapshots are available for the individual components of such assemblies (PCNA [Protein Data Bank (PDB) ID code: 1VYM], human 9-1-1 [3GGR]) (Fig. S1) and for two binary complexes [FEN1/DNA (3Q8L) and FEN1/PCNA (1UL1)] (3,16,(18)(19)(20)28), the larger ternary assemblies present Author contributions: J.Q.-A., S.E.T., J.A.T., P.K.C., E.N., and I.I. designed research; J.Q.-A., C.Y., X.X., S.E.T., M.-S.T., and I.I.…”
mentioning
confidence: 99%
“…This mechanism was proposed because studies in vitro showed that endonucleolytic cleavage by FEN1 is inhibited when the 5 0 end of the flap is blocked either with a complementary primer or a biotin-conjugated streptavidin moiety (Murante et al 1995). However, recent work has shown that FEN1 initially binds to the base of the flap causing a change in the substrate conformation that orients FEN1 in a manner that allows for precise cleavage (Gloor et al 2010;Tsutakawa et al 2011). The free 5 0 end of the flap is then threaded past or through the helical arch and active site of FEN1 permitting a single cleavage event (Gloor et al 2010).…”
Section: Pathways Of Eukaryotic Okazaki Fragment Processing Short Flamentioning
confidence: 99%